ANALISIS PENGARUH KUALITAS LAYANAN, BUNGA KOMPETITIF DAN KEMUDAHAN PROSEDUR TERHADAP KEPUASAN KONSUMEN (Studi Kasus Pada PT.Adira Dinamika Multifinance Tbk, Cabang Pontianak) - B31112008, KRISNO (Jurnal Manajemen Update, 2017)
The purpose of this study was to determine the effect of service quality, competitive interest and ease of procedure on customer satisfaction. In this research used type of causal research (causal research). Population in this research is customer of PT. Adira Dinamika Multifinance Tbk, Pontianak Branch. 100 (One Hundred) peoples used to be sample who represent customer satisfaction PT. Adira Dinamika Multifinance Tbk, Pontianak Branch taken by non-probability sampling method and data collection using questionnaire.The result of research show that the three independent variables namely service quality, competitive interest, and ease of procedure have a significant effect on dependent variable that is consumer satisfaction. The results of multiple regression testing showed that the variable that has the greatest influence is the ease of procedure shown by the value of regression coefficient X3 of 0.418 with a significance value of 0.000. Then followed by the competitive interest variable regression coefficient value X2 of 0.275 with a significance value of 0.004 while the low-affect variable is the quality of service with the value of regression coefficient X1 of 0.174 with a significance value of 0.026.Keywords: consumer satisfaction, service quality, competitive interest, and ease of procedure.